(untitled) (Journal of Hama University, 2025)
The research was conducted on (12) local pregnant dogs, aged (2-6) years and weighing (15-30) kg, who were placed in special boxes for dogs and under the same health and nutritional conditions at the College of Veterinary Medicine at the University of Hama. After diagnosing the pregnancy using an echography and several days before the date of birth, the animals were randomly divided into two groups, each group included six bitches: The first group: general anesthesia was used for the caesarean section: the sedative xylazine with ketamine. The second group: The two agents were used for caesarean section: the agent xylazine with the topical analgesic solution lidocaine 1%. Caesarean section was duly performed for the experimental animals, and clinical indicators (heart rate - rate of breathing movements - temperature rate) were recorded at time intervals (before injection - 15 minutes after injection - 30 minutes after injection - 60 minutes after injection - 120 minutes after injection) Some blood parameters were also recorded (red blood cell count - white blood cell count - platelet count). The results showed slight significant differences in clinical and hematological indicators when comparing the two groups between the different types of analgesics and drugs used. It is concluded from this research that injection of lidocaine with xylazine was the best in safe and time terms of side effects.